A 20-year-old woman with pulmonary embolism and deep vein thrombosis associated with May-Thurner syndrome - Yusuke Yamazaki, MD; Hidehiko Ikura, MD; Toru Egashira, MD, PhD; Toshimi Kageyama, MD; Masaru Shibata, MD; Kazunori Moritani, MD, PhD; Hideo Mitamura, MD, PhD (Radiology Case Reports)
May-Thurner syndrome (MTS) is a clinical condition characterized by the compression of the left common iliac vein between the overlying right common iliac artery and the underlying lumbar vertebrae. Although MTS can lead to deep vein thrombosis (DVT) and, in some cases, pulmonary embolism (PE), it remains underrecognized in clinical practice. We present a case of PE and DVT associated with MTS in a 20-year-old woman with a prolonged history of taking oral contraceptives (OCs). Initial computed tomography angiography (CTA) raised suspicion of MTS, which was further confirmed by Duplex ultrasonography. Anticoagulation therapy, along with discontinuation of OCs, resulted in resolution of thrombi in both the pulmonary and deep venous systems, with no recurrence following cessation of anticoagulation. This case underscores the importance of combining multiple imaging modalities in the evaluation of young women presenting with left-sided DVT, which eventually led to the diagnosis and proper management of MTS.